Crosstalk between metabolism and immunity: the 3rd Annual Research Symposium of Instituto Gulbenkian de Ciência. (4th June 2020) - Amin, Abdulbasit; Neves‐Costa, Ana; Pedroso, Dora; Colaço, Henrique; Coelho, Inês; Mahú, Inês; Badenes, Marina; Duarte, Nádia
Abstract : The 'Crosstalks of immunity and metabolism' Symposium was focused on how the intercommunication between different organs and the immune system affects organismal health. At this meeting, experts in immunology and metabolic research provided novel insights into the growing field of immunometabolism. This report attempts to review and integrate views, ideas, propositions, and conclusions that emanated from the symposium. Abstract : The recent interest in exploring interactions between immunity and metabolism has inspired the theme of the symposium, which we summarize in this report. This intersection has proven a fruitful approach in the dissection of mechanisms that regulate whole‐body physiology. A multidisciplinary panel of speakers presented research focused on the immunometabolic crosstalks that regulate health in the context of a variety of pathologic insults, such as infections, tissue damage, cancer, and obesity.